Effects of Organic Fertilizers and Neem-Coated Urea On Growth, Yield, Soil Nutrient Status and Cost Economics of Sesame (Bangladesh Journal of Botany, 2025)
An experiment was conducted to evaluate the effect of organic fertilizers and neem-coated urea on growth, yield, soil nutrient status and cost economics of sesame. Farmyard manure (FYM) @ 10 t ha⁻¹ significantly increased growth, with the highest test weight (2.87 g) and seed yield (349.4 kg/ha), followed by press mud cake @ 12.5 t ha-1 (M3). Among nitrogen treatments, 150% (S5) and 125% (S4) recommended dose of nitrogen (RDN) with neem-coated urea resulted in the highest seed yields (368.2 kg/ha and 353.4 kg/ha, respectively). The soil nutrient status showed increased nitrogen, phosphorus, potassium and organic carbon with organic amendments. Economic analysis revealed that M2S5 provided the highest net returns (₹20,258) and M3S5 exhibited the highest benefit-cost ratio (1.97). Thus, combining organic manures with neem-coated urea improves yield, soil health and economic returns in sesame.Bangladesh J. Bot. 54(4): 1069-1075, 2025 (December)